Nana Upstairs & Nana Downstairs - De Paola, Tomie (New York Puffin books, 2000)
Four-year-old Tommy enjoys his relationship with both his grandmother and great-grandmother, but eventually learns to face their inevitable death.
Keywords: Grandmothers -- Fiction; Great-grandmothers -- Fiction; Old age -- Fiction; Death -- Fiction